MISKONSEPSI SISWA DALAM MATERI PERSAMAAN LINEAR SATU VARIABEL DI SMP - Husna, Nurul (Educatio, 2019)
One of the mathematical material in class VII SMP is Persamaan Linier Satu Variabel (PLSV). Students experience obstacles. Distinguish ideas that belong to concepts and not concepts, and incorrectly define mathematical concepts. If thuis continues, there will be on going students 'misconceptions on material of the linear equation of one variable in class VII SMP N 2 Sebawi and the factors that cause students' misconceptions. The method used is descriptive qualitative. Subjects were 42 students. The result of data analysis showed: (1) the form and percentage of misconception that most students had, namely 85% of students could not distinguish examples and not PLSV examples and not PLSV examples, 97% of students ignored the equivalent simbol (?) in the PLSV competions process, 71,4% used procedures that are not in accordance with the conditions of completion, 66.7% of students incorrectly determine the number sign, 95.2% of students use the term move segment, 47.6% of students incorrectly determine the results of integer operations, 95.2% of students ignore the PLSV completion requirement, and 64.3% of students made inferences without the correct supporting reason: (2) The percentage of factors that cause the most students' misconceptions is 71% caused by students' preconceptions or false concepts, 71.4% is caused by students' associative thingking, and 90.3% is caused by incomplete reasoning.